1998
DOI: 10.1080/10643389891254197
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact and Mechanisms of the Biological Clogging of Saturated Soils and Aquifer Materials

Abstract: The biological clogging of natural porous media, often in conjunction with physical or chemical clogging, is encountered under a wide range of conditions. Wastewater disposal, artificial groundwater recharge, in situ bioremediation of contaminated aquifers, construction of water reservoirs, or secondary oil recovery are all affected by this process. The present review provides an overview of the techniques that are used to study clogging in the laboratory, or to monitor it in field applications. After a brief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
291
1
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(304 citation statements)
references
References 191 publications
(391 reference statements)
7
291
1
5
Order By: Relevance
“…This is in contrary to its behavior at decreasing water potential, where the pore size of sand may change up to four orders of magnitude by a shrinking biofilm [43]. [2] or [3] has shown that strong biofilm formation, eventually in conjunction with entrapped metabolic gasses may finally cause biological clogging by reducing the void volume and in consequence the soil permeability. [48] found same results for biological clogging in sand filters.…”
Section: Effect Influence Of Biofilm Formation On Horizontal Water Flowmentioning
confidence: 47%
“…This is in contrary to its behavior at decreasing water potential, where the pore size of sand may change up to four orders of magnitude by a shrinking biofilm [43]. [2] or [3] has shown that strong biofilm formation, eventually in conjunction with entrapped metabolic gasses may finally cause biological clogging by reducing the void volume and in consequence the soil permeability. [48] found same results for biological clogging in sand filters.…”
Section: Effect Influence Of Biofilm Formation On Horizontal Water Flowmentioning
confidence: 47%
“…Other authors have found strong links between microbial activity and water relations, either through pore blockage mechanisms under high substrate loads (Baveye et al 1998), or though increasing water repellency as shown in our previous work (Czarnes et al 2000). Plant root mucilages have also been well documented to increase aggregate stability (Watt et al 1993).…”
Section: Discussionmentioning
confidence: 87%
“…In addition, biofilm has the intrinsic ability of degrading certain compounds (Wood and Whitaker 1998). So, over the past several decades, the features of bioclogging and biodegradation in porous media with biofilm have given rise to a broad range of applications, such as bioremediation, biobarriers (Baveye et al 1998;Cunningham et al 1991;Mitchell et al 2009), microbial enhanced oil recovery (Afrapoli et al 2011), and protection of steel corrosion (Videla and Herrera 2009;Zuo 2007). A number of macroscale models for describing solute transport in porous media with biofilm are available in the literature (Baveye and Valocchi 1989;Cunningham and MendozaSanchez 2006;van Noorden et al 2010;Ebigbo et al 2010Ebigbo et al , 2012Kapellos et al 2007;Rittmann 1993;Thullner et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm occupies void pore spaces blocking water flow, which consequently reduces hydrodynamic properties of porous media like porosity and permeability. This leads to a condition known as bioclogging (see Baveye et al 1998). In addition, biofilm has the intrinsic ability of degrading certain compounds (Wood and Whitaker 1998).…”
Section: Introductionmentioning
confidence: 99%